Long‐term outcomes of primary cystocele repair by transvaginal mesh surgery versus laparoscopic mesh sacropexy: extended follow up of the PROSPERE multicentre randomised trial. (5th August 2021) - Lucot, J‐P; Cosson, M; Verdun, S; Debodinance, P; Bader, G; Campagne‐Loiseau, S; Salet‐Lizee, D; Akladios, C; Ferry, P; De Tayrac, R; Delporte, P; Curinier, S; et al.
Abstract : Objective: To compare the effectiveness and safety of laparoscopic sacropexy (LS) and transvaginal mesh (TVM) at 4 years. Design: Extended follow up of a randomised trial. Setting: Eleven centres. Population: Women with cystocele stage ≥2 (pelvic organ prolapse quantification [POP‐Q], aged 45–75 years without previous prolapse surgery. Methods: Synthetic non‐absorbable mesh placed in the vesicovaginal space and sutured to the promontory (LS) or maintained by arms through pelvic ligaments and/or muscles (TVM). Main outcome measures: Functional outcomes (pelvic floor distress inventory [PFDI‐20] as primary outcome); anatomical assessment (POP‐Q), composite outcome of success; re‐interventions for complications. Results: A total of 220 out of 262 randomised patients have been followed at 4 years. PFDI‐20 significantly improved in both groups and was better (but below the minimal clinically important difference) after LS (mean difference −7.2 points; 95% CI −14.0 to −0.05; P  = 0.029). The improvement in quality of life and the success rate (LS 70%, 61–81% versus TVM 71%, 62–81%; hazard ratio 0.92, 95% CI 0.55–1.54; P  = 0.75) were similar. POP‐Q measurements did not differ, except for point C (LS −57 mm versus TVM −48 mm, P  = 0.0093). The grade III or higher complication rate was lower after LS (2%, 0–4.7%) than after TVM (8.7%, 3.4–13.7%; hazard ratio 4.6, 95% CI 1.007–21.0, P  = 0.049)). Conclusions: Both techniques provided improvement and similar success rates. LS had a better benefit–harm balance with fewer re‐interventions due to complications. TVM remains an option when LS is not feasible. Tweetable abstract: At 4 years, Laparoscopic Sacropexy (LS) had a better benefit–harm balance with fewer re‐interventions due to complications than Trans‐Vaginal Mesh (TVM). Tweetable abstract: At 4 years LS had a better benefit–harm balance with fewer re‐interventions due to complications than TVM.